Analysis of Metaphorical Expressions Used in Adele’s Song Lyrics “Someone Like You” - Juliana Juliana; Santi Arafah; Fadhila Rahma Handayani; Fiore Arayu Hutagalung (Edumaspul: Jurnal Pendidikan, 2023)
Metaphorical expressions play a crucial role in music, enabling artists to communicate complex emotions and experiences through vivid and imaginative language. This research examined the metaphorical expressions used in the lyrics of Adele's famous song "Someone Like You." By analyzing the metaphorical utilization in this song, it can gain insight into Adele's poetic techniques for evoking strong emotions and establishing rapport with her audience. Using a qualitative methodology, this research begins by identifying and classifying the metaphorical expressions found in the lyrics of "Someone Like You." Examining metaphors at multiple levels, including conceptual metaphors and novel metaphors, reveals their underlying meaning and symbolism. In addition, the study explores the potential cultural, emotional, and psychological implications of these metaphors, casting light on the universal appeal of the song. The lyrics of "Someone Like You" are full of metaphors that depict emotional states, such as love as a journey, heartbreak as physical pain, and time as a healing force. Moreover, Adele's metaphors connect the audience with the songwriter's experiences, resonating with similar emotional journeys. The analysis highlights the effectiveness of metaphors in enhancing the song's lyrical impact and eliciting empathetic responses. Adele's use transforms "Someone Like You" into a universal anthem of sorrow and perseverance. This study contributes to the existing literature on metaphor analysis in music by analyzing the metaphorical expressions in Adele's "Someone Like You." It illustrates the ability of metaphors to encapsulate complex emotions and experiences, thereby enhancing the listener's comprehension and emotional engagement with the music.